2023
DOI: 10.3389/frvir.2023.1065863
|View full text |Cite
|
Sign up to set email alerts
|

Art as therapy in virtual reality: A scoping review

Abstract: This scoping review focuses on therapeutic interventions, which involve the creation of artworks in virtual reality. The purpose of this research is to survey possible directions that traditional practices of art therapy and therapeutic artmaking could take in the age of new media, with emphasis on fully immersive virtual reality. After the collection of papers from online databases, data from the included papers were extracted and analyzed using thematic analysis. The results reveal that virtual reality intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 86 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Demand for radically customizable VR therapy has been increasing in the literature (Baghaei et al, 2020;Halim et al, 2022), and some researchers have suggested VRET may lead to poor results if VR content does not match clients' personal experiences or expectations (Chard et al, 2023). Emerging techniques for the nontechnical creation of self-produced VR content should be examined for clinical potential in the hands of therapists and their clients (Brandstätter, 2023;Georgieva & Georgiev, 2022;Hadjipanayi et al, 2023;Schöne et al, 2023). Therapists in this study described how the proposed features of tele-VRET could also expand clinical options beyond exposure therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Demand for radically customizable VR therapy has been increasing in the literature (Baghaei et al, 2020;Halim et al, 2022), and some researchers have suggested VRET may lead to poor results if VR content does not match clients' personal experiences or expectations (Chard et al, 2023). Emerging techniques for the nontechnical creation of self-produced VR content should be examined for clinical potential in the hands of therapists and their clients (Brandstätter, 2023;Georgieva & Georgiev, 2022;Hadjipanayi et al, 2023;Schöne et al, 2023). Therapists in this study described how the proposed features of tele-VRET could also expand clinical options beyond exposure therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a tool's aesthetics influences the user's perception of its utility and formation of the user's persistent attitude towards the tool [HT06, JWTY16,YKW22], it is critical to understand how features impact users' understanding, emotions, and expectations the first moment they are perceived. While there is a substantial body of research on virtual reality (VR) and its use for art making [HBM23], there are limited studies that explore factors that influence the first-impressions of VR art experiences.…”
Section: Introductionmentioning
confidence: 99%